Nurses’ Caring Behaviour and Covid-19 Patient Satisfaction at RSUP Dr. M. Djamil Padang - Fadriyanti, Yessi; Astuti, Verra Widhi; Nidia, Wira Heppy; Renidayati, Renidayati (Universitas Aisyah Pringsewu, 2024)
This research is quantitative research, with a cross sectional study approach. This study aims to analyze the independent variable, namely the caring behavior of nurses, and the dependent variable, namely the satisfaction of Covid patients at RSUP Dr.M. Djamil Padang. The research was conducted from December 2020 – September 2021. The data analysis technique in this study used univariate analysis to see a picture of nurses' caring behavior and Covid patient satisfaction and bivariate analysis was used to determine the relationship between nurses' caring behavior and Covid patient satisfaction. Bivariate analysis was carried out using the chi-square test with a significance level of 0.05 (? = 5%) and a confidence interval of 95%. Based on the research results, the presentation of dissatisfied patient satisfaction was higher for bad nurses' caring behavior compared to good nurses' caring behavior (53.8%: 11.8%) with a p-value of 0.037. So we can draw the conclusion that more than half of the nurses' caring behavior is good in the Covid isolation room, the majority of patients are satisfied with the nursing services provided in the room, there is a significant relationship between caring behavior and patient satisfaction and there is a significant relationship between the five indicators of caring behavior and patient satisfaction.